The impact of Treasury supply on financial sector lending and stability - Krishnamurthy, Arvind; Vissing-Jorgensen, Annette (Journal of Financial Economics, 2015)
We present a theory in which the key driver of short-term debt issued by the financial sector is the portfolio demand for safe and liquid assets by the nonfinancial sector. This demand drives a premium on safe and liquid assets that the financial sector exploits by owning risky and illiquid assets and writing safe and liquid claims against them. The central prediction of the theory is that safe and liquid government debt should crowd out financial sector lending financed by short-term debt. We verify this prediction with US data from 1875 to 2014. We take a series of approaches to rule out standard crowding out via real interest rates and to address potential endogeneity concerns.